POCS-based reconstruction of multiplexed sensitivity encoded MRI (POCSMUSE): A general algorithm for reducing motion-related artifacts - Chu, Mei-Lan; Chang, Hing-Chiu; Chung, Hsiao-Wen; Truong, Trong-Kha; Bashir, Mustafa R.; Chen, Nan-kuei (Magnetic resonance in medicine, 2015)
Purpose A projection onto convex sets reconstruction of multiplexed sensitivity encoded MRI (POCSMUSE) is developed to reduce motion‐related artifacts, including respiration artifacts in abdominal imaging and aliasing artifacts in interleaved diffusion‐weighted imaging. Theory Images with reduced artifacts are reconstructed with an iterative projection onto convex sets (POCS) procedure that uses the coil sensitivity profile as a constraint. This method can be applied to data obtained with different pulse sequences and k‐space trajectories. In addition, various constraints can be incorporated to stabilize the reconstruction of ill‐conditioned matrices. Methods The POCSMUSE technique was applied to abdominal fast spin‐echo imaging data, and its effectiveness in respiratory‐triggered scans was evaluated. The POCSMUSE method was also applied to reduce aliasing artifacts due to shot‐to‐shot phase variations in interleaved diffusion‐weighted imaging data corresponding to different k‐space trajectories and matrix condition numbers. Results Experimental results show that the POCSMUSE technique can effectively reduce motion‐related artifacts in data obtained with different pulse sequences, k‐space trajectories and contrasts. Conclusion POCSMUSE is a general post‐processing algorithm for reduction of motion‐related artifacts. It is compatible with different pulse sequences, and can also be used to further reduce residual artifacts in data produced by existing motion artifact reduction methods. Magn Reson Med 74:1336–1348, 2015. © 2014 Wiley Periodicals, Inc.